Testing Asymmetric Cointegration Between Real Wage, Labour Productivity And Job Opportunity In South Africa : Array - Habanabakize, Thomas (Acta Universitatis Danubius. Œconomica, 2020)
Labour productivity and real wage are two dynamic economic indicators that, among many others, influence employment changes. Their effects on employment or job opportunities can either be positive or negative. This study investigates the asymmetric cointegration between real wage, labour productivity and job opportunity in South Africa between 1994 and 2018. The used methodology includes the application of a non-linear autoregressive distributed lag (NARDL) model, ECM and the dynamic multipliers. The obtained results from the bound testing suggested the existence of a long run relationship among the underlined variables. The estimated NARDL model revealed that real wage and labour productivity asymmetrically influence job opportunity dynamism. While positive component of productivity dominates over negative components; negative component of real wage dominates the positive component leading. Thus, labour productivity growth creates job opportunities whilst increase in real wage leads to a decline in the job opportunity. The study, therefore, recommends improvement in both labour productivity capacity through skills enhancement and real wage management through currency strengthening.